2014
DOI: 10.1371/journal.pcbi.1003632
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Human Tissue Interactomes Reveals Factors Leading to Tissue-Specific Manifestation of Hereditary Diseases

Abstract: An open question in human genetics is what underlies the tissue-specific manifestation of hereditary diseases, which are caused by genomic aberrations that are present in cells across the human body. Here we analyzed this phenomenon for over 300 hereditary diseases by using comparative network analysis. We created an extensive resource of protein expression and interactions in 16 main human tissues, by integrating recent data of gene and protein expression across tissues with data of protein-protein interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
97
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 53 publications
14
97
0
1
Order By: Relevance
“…In particular, we showed that when cellular signaling is studied in an infectious or genetic disease context, combining both gene expression information from the tissue affected by the disease and predicted network information flow, serves to highlight important mediators of disease from the PPI hairball surrounding the studied proteins (29). Indeed, disease-causing proteins tend to form an increased number of tissue-specific PPIs in the tissues that they affect (38). …”
Section: Resultsmentioning
confidence: 99%
“…In particular, we showed that when cellular signaling is studied in an infectious or genetic disease context, combining both gene expression information from the tissue affected by the disease and predicted network information flow, serves to highlight important mediators of disease from the PPI hairball surrounding the studied proteins (29). Indeed, disease-causing proteins tend to form an increased number of tissue-specific PPIs in the tissues that they affect (38). …”
Section: Resultsmentioning
confidence: 99%
“…Although the expression of many disease-associated proteins is not tissue-specific, many protein misfolding diseases exhibit tissue-specific vulnerability [71, 72]. For example, mutations in the ubiquitously expressed co-chaperone DNAJB6 cause a tissue-specific disease, limb-girdle muscular dystropy [18].…”
Section: Discussionmentioning
confidence: 99%
“…(9,12,13)). The value of the resulting tissue-sensitive interaction networks (interactomes) was demonstrated in several applications, where tissue interactomes were shown to outperform the global, unfiltered interactome, in prioritizing disease genes (1216) or to illuminate the molecular basis of tissue-selective hereditary diseases (17). …”
Section: Introductionmentioning
confidence: 99%
“…As we previously showed, this comparison is key in studying the tissue-specific effects of disease proteins (17). TissueNet v.2 is an enhanced version of TissueNet that includes significant data expansion, increased usability, and provides a new quantitative view of the query protein and its tissue-associated interactions.…”
Section: Introductionmentioning
confidence: 99%